Perilaku Penggunaan Smartphone Pada Kalangan Remaja - - AMIK BSI Purwokerto, Fahlepi Roma Doni (APMMI - Asosiasi Profesi Multimedia Indonesia, 2017)
Abstract - The current information technology is growing very rapidly. As for that technology such as Smartphones, computers and technology equipment and the like which are the tools created to facilitate our work as its users. Results of innovation in the field of information technology in developing software or hardware on an ongoing basis, it has shorten the age of technical and economical lifespan of software as well as hardware before. This fact brings the user (end user) is always vying for increased pengguaan the latest technology. With the development of technology intensified this smartphone, is slowly making its users increasingly dependency to use Smartphones. This fact brought positive impact and negative effects for the user (end user). The use of Smartphones bring so much convenience for its users. With all the facilities provided by the smartphone. But behind the ease of the presence of the smartphone also brings a downside for the behavior of the users. The most noticeable impact and the damage is by smartphone users can access content langgsung-content the wanton unscrupulous which can easily be accessed by Smartphones via the internet. Research undertaken aims to examine the behavior of the use of smartphones in among teenagers approach model of Everyday life information case study on Campus BSI Tangerang, and then tested with path analysis using Software Analysis of Moment Structure.Keywords: Smartphone, information technology, Model of Everyday life informationÂ Abstrak - Teknologi informasi saat ini berkembang sangat pesat. Adapun teknologi itu seperti smartphone, komputer dan peralatan teknologi semacamnya yang merupakan peralatan yang diciptakan untuk mempermudah pekerjaan kita sebagai penggunanya. Hasil inovasi di bidangÂ teknologi informasi dalam mengembangkan perangkat lunak maupun perangkat keras secara berkelanjutan, telah mempersingkat umur teknis dan umur ekonomis dari perangkat lunak maupun perangkat keras sebelumnya. Kenyataan ini membawa pengguna (end user) selalu berlomba-lomba untuk meningkatkan pengguaan teknologi terbaru tersebut. Dengan adanya perkembangan teknologi smartphone yang semakin pesat ini, secara perlahan membuat penggunanya semakin ketergantungan untuk menggunakan smartphone. Kenyataan ini membawa dampak positif dan dampak negatif bagi pengguna (end user). Penggunaan smartphone membawa begitu banyak kemudahan bagi penggunanya. Dengan segala fasilitas yang disediakan oleh smartphone. Namun dibalik kemudahan tersebut kehadiran smartphone juga membawa sisi buruk bagi perilaku penggunannya. Dampak yang paling nyata dan merusak adalah dengan smartphone penggunanya dapat langgsung mengakses konten-konten asusila yang tak bermoral yang dengan mudah dapat diakses dengan smartphone melalui internet. Penelitian yang dilakukan bertujuan untuk mengkaji perilaku penggunaan smartphone pada kalangan remaja pendekatan model of Everyday life information studi kasus pada Kampus BSI Tangerang, dan kemudian diuji dengan Analisis Jalur menggunakan Software Analysis of Moment Structure.Kata Kunci: Smartphone, Teknologi Informasi, Model of Everyday Life Information